THE IMPACT CORPORATE GOVERNANCE ON INTERNET FINANCIAL REPORTING: EMPIRICAL EVIDENCE FROM PALESTINE - Barakat, Firas S. Q.; Perez, M. Victoria Lopez; Ariza, Lázaro Rodríguez; Barghouthi, Orobah Ali; Islam, K. M. Anwarul (International Journal of Accounting & Finance Review, 2020)
The current research investigates whether the difference in the Internet Financial Reporting standard is clarified by corporate governance. A study was carried out on a selection of 48 companies listed on the 2019 Palestine Stock Exchange. An index was also selected from several previous studies to assess the standard of Internet financial reporting. One of the first analytical researches to investigate the relationship between corporate governance and Internet Financial Reporting in Palestine is the latest analysis. Firstly, the scope of disclosure of Internet Financial Reporting in Palestinian businesses appears to be limited. Second, the educational history of boards is greatly related to Internet Financial Reporting. Nevertheless, the board independence coefficient and board audit committee are negligible. Thirdly, an important element in strengthening internet financial reporting standards is a broad audit company. Fourthly, there is a strong positive correlation between the concentration of ownership and financial reporting on the Internet. Companies mainly held by stakeholders are more likely to reveal internet data and to strengthen the reports released. Finally, profitability and market capitalization have a direct connection with Internet Financial Reporting, and Internet Financial Reporting does not justify the composition of the board, board meetings, international investors, and business size.